Baking spirits bright - Fox, Sarah (Mystery writer) (Fox, Sarah (Mystery writer). True Confections mystery., 2023)
"Winter has arrived in Larch Haven, Vermont, bringing with it holiday cheer, lots of snow, and freezing temperatures. Becca Ransom is squeezing in time to skate on the frozen canals and drink hot chocolate by a roaring fire while also whipping up new creations for her family's chocolate shop and experimenting with holiday flavors like eggnog, gingerbread, and peppermint. At the same time, Becca is preparing for the Baking Spirits Bright holiday baking competition, a popular annual event. She's planning to enter an edible model of Larch Haven, with a mountain backdrop made of cake, gingerbread cottages, and chocolate gondolas on sugar-glass canals. Professional bakers and a local food blogger are also participating in the event and they aren't about to go down without a fight. The competition quickly heats to a boiling point, with flaring tempers and mysterious happenings. When one of the entrants is found dead, stabbed with Becca's chocolate chipper, Becca tries to salvage the season by finding the killer. But the heat is on, and Becca is in danger of getting burned"--